UTILIZATION OF THE GREAT MOSQUE OF SINGKAWANG HISTORY LEARNING RESOURCES - Haris Firmansyah (Jurnal Scientia, 2023)
West Kalimantan is one of the provinces in Indonesia. This province has several cities and regencies, one of which is Singkawang which has a historical site, the Great Mosque of Singawang City. Although it has not been included in the cultural heritage, the minaret and sovereignty monument in the mosque have been made as cultural heritage. The primary source in the research was obtained through observation and direct interviews with speakers in the mosque, while the secondary source was documentation. The subject of this study is a student of the history education study program class of 2021. In this study using descriptive-qualitative method. The results of this study are as follows: The Great Mosque of Singkawang is a large mosque built around 1880. This mosque has a unique architecture with traditional Islamic style. In general, the architecture of the Singkawang Grand Mosque has two floors, which follows the form of mosque buildings in the Middle East. Among them there is a small mosque dome that has existed since the first time this mosque was built. The historical education study program utilizes the Singkawang Grand Mosque as a form of learning through a course called Field Work Lecture or (KKL), which plunges directly into the field and sees firsthand the historical relics that still exist inside and outside the building.